Impact Evaluation of Government Asistance on the Improvement of Quality of Vocational Education - Aziz Wahyu Suprayitno (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2021)
This study evaluates the impact evaluation of Government Assistance on the improvement of Quality of Vocational Education. This study using the Difference in Difference (DID) method to estimate the effects of Government Assistance allocation by comparing the changes in outcome quality of Vocational Education measured by School Quality Report (Rapor Mutu Sekolah) that contains a number with scale 1 – 7 between the Vocational High School that get Government Assistance (intervention/treatment group) and the Vocational High School that did not (control group), using regression model by testing parallel trend assumption first. Secondary data consists of Government Assistance and Vocational High School Quality Report for 2013 – 2018 from the Directorate of Vocational Education, Ministry of Education and Culture. Government Assistance data selected is only Assistance for facilities/infrastructure and Assistance for rehabilitation/construction of buildings using a purposive sampling technique. The results showed that the average value of the Vocational High Schools that received Government Assistance was higher by 0.0373 compared to Vocational High Schools that did not receive Government Assistance, after the intervention of Government Assistance from 2016 - 2018. That results indicates that Government Assistance has a positive impact on improving the Quality of Vocational Education. Keywords : impact evaluation, DID, quality of vocational education, government assistance.